Services liberalization in the new generation of Preferential Trade Agreements (PTAs): How much further than the GATS? - Martin Roy; Juan Marchetti; Hoe Lim (World Trade Organization (WTO), 2006)
This paper attempts to fill a gap in the trade literature by providing a comprehensive overview of services liberalization commitments in the new generation of preferential trade agreements (PTAs) as compared to prevailing GATS commitments and Doha Round offers. By developing a new database, the paper reviews the commitments undertaken by 29 WTO Members (counting the EC as one) under mode 1 (cross-border supply) and mode 3 (commercial presence) in 28 PTAs negotiated since 2000. The paper presents a general analysis from both a cross-country and cross-sector perspectives, and also examines in more detail the GATS+ commitments undertaken in a number of key sectors (audiovisual, distribution, education, financial, professional, and telecommunication services). The paper also discusses the potential economic costs arising from these preferential agreements, as well as the potential implications for the multilateral trading system, and for the Doha round of negotiations in particular. The paper concludes by discussing possible approaches to overcome the potential downsides of PTAs, including proposals for a more pro-active role for the WTO in the surveillance of these agreements.
Keywords: F10; F13; L8; F2; 330; GATS; trade in services; regionalism; preferential trade agreements; Internationaler Dienstleistungsverkehr; GATS; Außenhandelspräferenz; Welt